CORRELATION OF TOTAL ANTIOXIDANT STATUS (TAS) WITH DNA DAMAGE IN HIV/AIDS PATIENTS - Kolgiri, Vaishali; Patil, V. W.; Nagar, Vidya (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Abstract Â Title: Correlation of total antioxidant status (TAS) with DNA damage in HIV/AIDS patients. Â Background: The antioxidant deficiency in HIV-positive populations is probably due to increased utilization of antioxidant micronutrients because of increased oxidative stress rather than to inadequate dietary intake [1]. Â Objectives: The study had 2 principal objectives. The first was to determine total antioxidant status (TAS) and DNA damage in HIV /AIDS patients on varying antiretroviral therapy(ART) Â and those not on ART. The second objective was to ascertain whether there is any correlation between TAS and oxidative DNA damage in these patients. Â Design: This was a cross-sectional study involving 300 HIV positive and 100 HIV-negative subjects aged 20â€“60 yrs. Â Results: The varying ART has not have much effect on TAS levels but there was different levels of DNA damage in ART first line, ART second line and ART not yet started patients. There is a negative correlation between TAS & DNA damage. Â Conclusions: In this study, we observed that ART plays a significant role in the oxidative DNA damage. Decreased TAS is associated with increased DNA damage.Â Â